Operationalizing resilience: A content analysis of flood disaster planning in two coastal cities in Central Java, Indonesia - Handayani, Wiwandari; Fisher, Micah R.; Rudiarto, Iwan; Sih Setyono, Jawoto; Foley, Dolores (International journal of disaster risk reduction, 2019)
Global concern has sought to connect resilience with the field of disaster risk reduction, which was prominent in the Hyogo Framework for Action (2005–2015) and updated in the Sendai Framework for Disaster Risk Reduction (2015–2030). However, defining disaster risk reduction and resilience as policy goals geared towards reducing vulnerability and minimizing risk requires a closer examination. This research examines operationalization of resilience in programs and budgets of development plans in Indonesian cities. This paper investigates the documentation of planning policies in the Indonesian context, examining National to local level efforts. The research specifically analyzes case studies at two cities, Semarang and Tegal, and highlights how these sites have accommodated the term resilience to address flooding. The scope of the research focuses on flooding as it is the most commonly experienced hazard across Indonesia. Content analysis is applied to assess identified planning documents. The content analysis is further verified through focus group discussions among key stakeholders. Findings indicate that there are fourteen areas of plans/programs in terms of reduced exposure to hazards, lessened vulnerability of people and property, improved management of land and the environment, and improved preparedness to address flooding in the two selected cities. The elaboration of resilience-related programmes provides important lessons, namely that operationalizing resilience should be integrative and comprehensive, and require both short-term actionable initiative(s) and long-term transformative frameworks.